Local climate change and urban heat island mitigation techniques – the state of the art - Akbari, Hashem; Cartalis, Constantinos; Kolokotsa, Denia; Muscio, Alberto; Pisello, Anna Laura; Rossi, Federico; Santamouris, Matheos; Synnef, Afroditi; Wong, Nyuk Hien; Zinzi, Michele (Journal of Civil Engineering and Management, 2015)
Increase of the ambient air temperature in cities caused by the urban heat island phenomenon has a seri- ous impact on the economic and social system of cities. to counterbalance the consequences of the increased urban temperatures important research has been carried out resulting in the development of efficient mitigation technologies. the present paper aims to present the state of the art in terms of local climate change and urban heat island mitigation techniques. In particular, developments in the field on highly reflective materials, cool and green roofs, cool pavements, urban green and of other mitigation technologies are presented in detail, while examples of implemented projects are given.